6. POSTOPERATIVE OUTCOMES AND NURSING CARE IN PATIENTS UNDERGOING HIP REPLACEMENT AT TRANSPORT HOSPITAL 2024 (Vietnam Journal of Community Medicine, 2026)
Objective: To investigate common postoperative events and evaluate nursing care outcomes in patients undergoing hip replacement at the Department of Orthopedics, Transport Hospital.Methods: A retrospective, cross-sectional descriptive study was conducted on 65 inpatients who underwent hip replacement surgery between January and December 2024. Data were collected from medical records and analyzed using SPSS 20.0.Results: Postoperatively, 50.8% of patients reported severe pain and 32.3% experienced extreme pain. Edema occurred in 24% of patients, and 6.2% had significant wound discharge. Drainage volume was mainly 300–500 ml (60%), while 6.2% exceeded 1000 ml. Blood transfusion was required in 36.9% of patients, with 23.8% receiving more than 1000 ml. Early complications included bleeding (3.1%), dislocation (1.5%), and pressure ulcers (4.6%). Hospital stay longer than 10 days was observed in 60% of patients. At discharge, 70.8% could walk with assistive devices, 21.5% could stand, and 7.7% were unable to stand. Patient satisfaction was high, with 73.8% very satisfied and 21.5% satisfied.Conclusion: Patients undergoing hip replacement frequently experienced postoperative complications such as pain, edema, bleeding, dislocation, and pressure ulcers. Although hospital stay was relatively long, functional recovery outcomes were favorable, and most patients reported high satisfaction with nursing care.
Keywords: Hip replacement, postoperative, nursing care.